Murine thymic selection quantified using a unique method to capture deleted T cells - Stritesky, Gretta L. (National Academy of Sciences, 2013)
Thymic positive and negative selection events generate a T-cell repertoire that is MHC restricted and self-tolerant. The number of T cells undergoing positive and negative selection in normal mice has never been firmly established. We generated mice that lack the proapoptotic molecule Bim (bcl2l11) together with a Nur77(GFP) transgene, which allowed the identification and enumeration of T cells that would normally undergo clonal deletion. Using this method, we report the striking observation that six times more cells undergo negative selection than complete positive selection. Seventy-five percent of the negatively selected cells are deleted at the double positive stage in the thymic cortex, compared with 25% at the single positive stage in the medulla. The fact that more thymocytes are highly reactive to MHC than are weakly reactive is inconsistent with a random model of recognition and suggests that T-cell recognition is MHC biased. Furthermore, Bim(−/−) mice had an increased number of GFP(hi) cells in the peripheral lymphoid tissue and a corresponding increase in antigen experienced or anergic cell phenotype. Our data also show that the CD4+ T cells that are clonally deleted experienced only slightly stronger T-cell receptor signaling than those that developed into regulatory T cells.